Industry 4.0 And Training Factories for Data Generation and Verification - Miroslav MALAGA; Zdeněk ULRYCH (Communications of International Proceedings, 2021)
The paper is a short research of articles published mainly in the Web of Science (WoS) and Scopus databases, focused on the use of hardware models for data collection, creation of digital twins, or e.g. for verification of new algorithms, optimization of processes and algorithms, education of students, employees, etc. This research will serve as a basic overview of the possibilities, the building blocks and important parts used and how to manage them for a PhD project focused on data collection by industrial engineers from a learning/teaching factory.
Keywords: Industry 4.0; Hardware simulation; Simulation; Optimization; Production planning